Instructions influence response to the Chinese version of the Movement‐Specific Reinvestment Scale in community‐dwelling older adults. Issue 12 (4th November 2015) - Wong, Thomson WL; Abernethy, Bruce; Masters, Rich SW
Abstract : Aim: To examine whether differences emerged when the Chinese version of the Movement‐Specific Reinvestment Scale (MSRS‐C) was administered to community‐dwelling older adults with instructions to respond in the context of "general" movements, walking, using chopsticks or dressing. Furthermore, the difference between the six‐point Likert scale and four‐point Likert scale response formats of the MSRS‐C was investigated. Methods: The study was implemented in the community of Hong Kong with 52 older adults (mean age 77.4 years). Telephone interviews were carried out on two occasions for each participant. Participants provided a verbal response to each of 10 questions from the MSRS‐C with different response formats (i.e., six‐point or four‐point Likert Scales) and different instructions in the response context (i.e. general, walking, using chopsticks, dressing). The sequence of response format and context was randomized for each participant. Results: Older fallers scored significantly higher on the MSRS‐C (general) with six‐point or four‐point response formats than non‐fallers. The MSRS‐C (general) and MSRS‐C (walking) were not statistically different, and showed good discriminative power for previous older fall status (older fallers or older non‐fallers). However, MSRS‐C (chopsticks) and MSRS‐C (dressing) failed to differentiate older fallers from older non‐fallers. Conclusion: Both the MSRS‐C (general) and MSRS‐C (walking) with a six‐point or a four‐point response format showed good discrimination of older fallers from non‐fallers. Older adults might respond to the MSRS‐C with respect to the most challenging movements (e.g. fall‐related movements) in their daily living.Geriatr Gerontol Int 2016; 16: 1305–1311.